Seção de choque dos espalhamentos elétron-pósitron e Bhabha à temperatura finita no contexto de violação da simetria de Lorentz - Souza, Pablo Rodrigo Alves de (2021)
In this work we investigate the effects of the violation of the Lorentz and CPT symmetries on two wellknown processes in quantum electrodynamics, the eletcron-positron process and the Bhabha scattering, and both in the context of finite temperature. The violation mechanism is explicitly implemented via a non-minimal covariant derivative, constructed with a rank-4 background tensor field coupled to the electromagnetic field intensity; while temperature is introduced via the formalism of the thermal field dynamics. Such tree-level inclusions, in addition to reproducing the term in e 4 proportional cross section similar to that obtained from the usual version, also provide us with new vertex contributions proportional to the square of the coupling constant of the violation sector, λ 2 ; in addition to temperature being strongly present as a global factor in the total cross section of the process. Additionally, the conventional cross section resumes under the λ and T boundary conditions tending to zero, as expected.